2011
DOI: 10.1002/eji.201141870
|View full text |Cite
|
Sign up to set email alerts
|

The gene expression profile of phosphoantigen‐specific human γδ T lymphocytes is a blend of αβ T‐cell and NK‐cell signatures

Abstract: Global transcriptional technologies have revolutionised the study of lymphoid cell populations, but human cd T lymphocytes specific for phosphoantigens remain far less deeply characterised by these methods despite the great therapeutic potential of these cells. Here we analyse the transcriptome of circulating TCRVc 1 cd T cells isolated from healthy individuals, and their relation with those from other lymphoid cell subsets. We report that the gene signature of phosphoantigen-specific TCRVc 1 cd T cells is a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 57 publications
4
48
0
Order By: Relevance
“…This study adds a further facet to the pattern of Vδ2 T-cell gene expression, which has been described as being intermediate between αβ T cells and natural killer cells (26). The results of our present investigation extend these previous studies by demonstrating that gene expression is differentially regulated in human Vδ2 T cells by cognate TCR antigen BrHPP and A/E beads, and TGF-β/IL-15 cytokines provide an additional layer of regulation.…”
Section: Discussionsupporting
confidence: 81%
“…This study adds a further facet to the pattern of Vδ2 T-cell gene expression, which has been described as being intermediate between αβ T cells and natural killer cells (26). The results of our present investigation extend these previous studies by demonstrating that gene expression is differentially regulated in human Vδ2 T cells by cognate TCR antigen BrHPP and A/E beads, and TGF-β/IL-15 cytokines provide an additional layer of regulation.…”
Section: Discussionsupporting
confidence: 81%
“…GSE27291) and six adult blood αβ T-cell samples (accession nos. GSE15659 and GSE8059) were obtained from the National Center for Biotechnology Information Gene Expression Omnibus (55). Primers to quantify gene expression within sorted Vγ9Vδ2 γδ T cells, non-Vγ9Vδ2 γδ T cells, and αβ T cells were selected from PrimerBank (91) or were designed using Primer Express 2.0 (Applied Biosystems) (SI Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…Several adapter proteins [DNAX-activation protein 10 (DAP10), DAP12] and signaling molecules, such as phospholipase C, gamma 2 (PLCG2), PI3K, and CD3zeta, described as being associated with NKR signaling, were enriched as well (SI Appendix, Table S6) (54). Th1 bias, proinflammatory nature, and enrichment in NK genes also have been described as selective features of adult Vγ9Vδ2 T cells as compared with adult αβ T cells (55); comparison with adult Vγ9Vδ2 T-cellenriched genes showed that indeed several also were enriched in fetal Vγ9Vδ2 T cells (SI Appendix, Table S9). Vice versa, various fetal Vγ9Vδ2 T-cell-enriched genes (such as a series of transcription factors including PLZF) but not all (e.g., DAP10 and granzyme A) also were enriched in adult Vγ9Vδ2 T cells (SI Appendix, Table S6).…”
Section: Fetal Blood Cdr3γ9 Is Highly Restricted and Enriched For Thementioning
confidence: 99%
“…Transcriptome raw data files were downloaded from the GSE27291 dataset available at the National Center for Biotechnology Information repository Gene Expression Omnibus database (39). These comprised 12 samples of TCRVg9 + gd cells highly purified (.98% purity) from PBMC: four "resting control" samples, four "6 h after BrHPP activation" samples, and four "7 d after BrHPP activation" samples.…”
Section: Il1rl1 Gene Expression Analysismentioning
confidence: 99%